Анализ проектов создания кластеров в рекреационном секторе Николаевской области - Яцунский, Е. А. (НТУ "ХПИ", 2015)
Проведен анализ существующей рекреационной сферы Николаевской области, позволяющий разработать новые направления бизнеса, в том числе в новых секторах экономики, приведены рекомендации по устранению ранее допущенных недочетов в перспективе построения модели рекреационного кластера.

The analysis of the existing recreational sphere of Mykolayiv region was made. It allows to develop new lines of business, including in the new sectors of the economy. The recommendations to address deficiencies, which were previously admitted were provided so to build a model of recreational cluster in perspective.
The analysis of cluster formation projects in recreational sector of Nikolayev region
Keywords: Украина; процессы модернизации; рекреация; рекреационные кластеры; синергия; кластерный подход; recreation; recreation cluster; synergy; prospects of recreation; Ukraine; Nikolayev region